Detection of Objects Buried in the Sea Bottom with the Use of Parametric Echosounder - Eugeniusz KOZACZKA; Grazyna GRELOWSKA; Sławomir KOZACZKA; Wojciech SZYMCZAK (Archives of Acoustics)
The paper contains results of a in situ research main task of which was to detect objects buried, partially or completely, in the sea bottom. Object detecting technologies employing acoustic wave sources based on nonlinear interaction of elastic waves require application of parametric sound sources. Detection of objects buried in the sea bottom with the use of classic hydroacoustic devices such as the sidescan sonar or multibeam echosounder proves ineffective. Wave frequencies used in such devices are generally larger than tens of kHz. This results in the fact that almost the whole acoustic energy is reflected from the bottom. On the other hand, parametric echosounders radiate waves with low frequency and narrow beam patterns which ensure high spatial resolution and allows to penetrate the sea bottom to depths of the order of tens of meters. This allows to detect objects that can be interesting, among other things, from archaeological or military point of view.